Endoscopic sigmoidopexy for recurrent sigmoid volvulus in inoperable patients: a retrospective series of 15 patients - Ouazana, Salome; Coron, Emmanuel; Le Rhun, Marc; Le Rhun, Marianne; Dray, Xavier; Quénéhervé, Lucille (Endoscopy, 2022)
Background Recurrent sigmoid volvulus is frequent and sometimes occurs in frail patients with contraindications to surgical sigmoidectomy. Percutaneous endoscopic sigmoidopexy (PES) has recently been proposed as an alternative to elective sigmoidectomy. We aimed to describe the efficacy and safety of PES.Methods All consecutive patients who underwent PES for recurrent sigmoid volvulus at two French centers between January 2017 and March 2021 were included in this retrospective case series. Recurrent sigmoid volvulus was defined as at least two symptomatic episodes treated by endoscopic decompression. Under endoscopic guidance, anchors were placed to attach the sigmoid to the anterior abdominal wall, allowing the placement of pigtail Chait catheters.Results 15 patients (60 % female; median age 74 years [range 49–96]) were included. Median number of previous sigmoid volvulus episodes was 3 (range 2–6). Procedures were technically successful with no intraprocedural adverse events for 14 patients (93 %). Peritonitis occurred at Day 2 in one patient (serious adverse event rate 7 %). Median follow-up time was 10 months (range 1–30). No sigmoid volvulus recurrence occurred during follow-up.Conclusion PES using Chait catheters was feasible and effective for recurrent sigmoid volvulus and should be considered as an alternative to sigmoidectomy in inoperable patients.